2017
DOI: 10.1016/j.ekir.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Patients Treated for Hepatitis C Using a Sofosbuvir-based Regimen

Abstract: IntroductionThere is paucity of data on sofosubvir (SOF)−based therapy in patients on maintenance hemodialysis (MHD). The objective of this report is to describe our experience using SOF-based direct antiviral agent (DAA) therapy in MHD patients in India.MethodsAll patients on MHD and treated with SOF-based therapy were included in this study. Before starting treatment, viral load, genotype, liver fibroscan, and upper gastrointestinal endoscopy were performed in all patients. SOF 400 mg/d or on an alternate da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
3
37
0
1
Order By: Relevance
“…SVR rate in his study was 95.2%. Most of the patients in the RBV group (n = 23; 56%) required an increase in the erythropoietin dose; however, no patients discontinued therapy because of complications . The lower SVR rate in our haemodialysis cohort may be related to the small number of patients and the difference in RBV and SOF dosage.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…SVR rate in his study was 95.2%. Most of the patients in the RBV group (n = 23; 56%) required an increase in the erythropoietin dose; however, no patients discontinued therapy because of complications . The lower SVR rate in our haemodialysis cohort may be related to the small number of patients and the difference in RBV and SOF dosage.…”
Section: Discussionmentioning
confidence: 82%
“…Though smaller doses of the drug (200 mg/d or 400 mg on alternate day) were used by some investigators, several authors showed lower SVR rates with such doses . On the other hand, high efficacy and safety of full dose SOF‐containing regimens in patients with severe renal impairment were also demonstrated by many investigators …”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐three patients (37%) had complications while on therapy; 13 (20.3%) had dyspepsia, 4 (6%) had tuberculosis, and 3 (5%) had bacterial pneumonia. Twenty‐three patients (56%) in the RBV group had worsening anemia, requiring an increase in the erythropoietin . Further studies are required to better establish the role of sofosbuvir‐based regimen in CKD stages 4 to 5 and ESRD.…”
Section: Review Of Daa Combinations In Ckd and Kidney Transplant Recimentioning
confidence: 99%
“…However, the issue related to DAAs that various DAA drugs are not universally available in all countries 12 . Like in Pakistan, only SOF and subsequently Daclatasvir were available in 2015 to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Like in Pakistan, only SOF and subsequently Daclatasvir were available in 2015 to 2017. Because of suboptimal SVR, higher cost, and the moderate degree of adverse effects of IFN-based therapy, there was an intense interest in using DAAs in patients with endstage renal disease 12 .…”
Section: Introductionmentioning
confidence: 99%